ANALISIS DEFECT PRODUK SENAR PADA PROSES CELUP DENGAN PENDEKATAN DMAIC DI PT. CENTRAL SARANA PANCING PURBALINGGA - Nurjannah, Anisa; Prakoso, Indro; Faizah, Jihan (Journal of Industrial Engineering and Technology, 2023)
PT. Central Sarana Pancing is a company engaged in the manufacturing of fishing line and various fishing accessories. From the results of field observations that have been carried out, dyeing division is the division with the highest number of defects. From the define stage, the defects that occur in the string dyeing process are pigment sticking defects with a percentage of 49%, 38% non-standard color, 12% creasing, and 2% non-standard strength. From the DPMO calculation, Motorola's sigma value is 3.36, which means that the dyeing division is in the industry average category with a fairly large amount of quality costs, namely 25-40% of sales. From the analysis stage, the defects that occur are mostly caused by human or operator factors. Therefore, for the prevention and repair of defects is by improving the performance and accuracy of operators and employees must receive training and education in understanding the entire process being carried out. In addition, SOPs will be made for the improvements that will be carried out as a reference for employees in carrying out the production process at PT. Central Fishing Facilities. As for the mechanical aspect, it is necessary to clean working tools and machines and maintain them regularly.